Analisis Pengaruh Rasio Profitabilitas, Solvabilitas, dan Aktivitas terhadap Harga Saham - Dewi Oktavia; Bambang Sugeng Dwiyanto (Jurnal Manajemen Strategis: Jurnal Mantra, 2024)
This research aims to detect the magnitude of the influence of return on assets (ROA), debt to equity ratio (DER), and total assets turnover (TATO) on company share prices in the electronic retail sub-sector industry listed on the Indonesia Stock Exchange (BEI) for the year 2020-2021. The population in this study is five companies. The purposive sampling method was used to determine the sample. Multiple linear regression analysis techniques were used as the analysis method in this research. The results of the coefficient of determination analysis show that 36% of the sample variations in ROA, DER, and TATO can explain variations in stock prices. The findings in this research show that the influence of ROA, DER, and TATO simultaneously has a significant positive effect on stock prices. Meanwhile, the ROA and TATO variables have a negative and insignificant impact on share prices. Meanwhile, the DER variable has a positive and significant influence on share prices in the electronic retail sub-sector industry listed on the Indonesia Stock Exchange during 2020-2021.